Airports as a catalyst for regional labor market development and employment growth in the opinion of their stakeholders - Agnieszka Aleksandra Wilczyńska-Strawa; Stanisław Sirko; Marzena Piotrowska-Trybull (Journal of Modern Science)
Objectives Surveys were carried out in 2021, 2022 and 2023 to determine how residents of municipalities, representatives of municipal authorities and airport representatives, perceive the impact of the airport on the socio-economic situation of the municipality in which they are located, including the labor market.